ANALISIS LEAN SERVICE UNTUK MENGURANGI WASTE PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA MOUNTALA ACEH BESAR - Heri Tri Irawan; Iing Pamungkas; Arhami Arhami (Universitas Teuku Umar, 2018)
Tirta Mountala Regional Water Company (PDAM) is a regional company that has a concentration in the field of water supply. This study aims to implement Lean Service at PDAM Tirta Mountala in an effort to reduce waste in the service of installing new pipe connections. The method used in the study uses Big Picture Mapping and Root cause analysis in finding the causes of waste. The study was conducted in several stages, namely preliminary observations then continued with determining the use of the methods used, collecting data, conducting data processing, analyzing the results of data processing and finally concluding the results of the research, as well as being reviewed from lean service theories, The Waste that occurs is Over Production, Defect, Unnecessary Inventory, Inappropriate Processing, Excessive Transportation, Waiting, Unnecessary Motion. While the critical waste that occurs in the service process is waiting with a weight of 0.36. Waste waiting is caused by mechanical power delay, material repair delay, delay in repairing pipelines passing through public spaces. By knowing the types of waste and critical waste in PDAMs, it is expected to reduce waste and customer satisfaction is fulfilled.